Perawatan Payudara Terhadap Kelancaran Produksi ASI pada Ibu Post Partum - Fatia Sandra Kairupan; Irma M Yahya; Irne W Desiyanti (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Breast care is very important for mothers because it is a care action performed by the patient or assisted by others, usually starting from the first or second day after giving birth.The objective of this study is to determine the effect of breast care on the smoothness of breast milk production in postpartum mothers at RSUD Walanda Maramis.The research uses a quasi-experimental one-group post-test only design.The sample in this study consisted of 15 respondents.Data collection on breast milk smoothness used observation sheets and the statistical test employed was the independent t-test.The research results showed that the highest breast milk production after the intervention was smooth breast milk from 11 respondents (73.3%).The results of the unpaired t-test showed a p-value of 0.000 where < α 0.05.Conclusion: There is an influence of breast care on the smoothness of breast milk production in postpartum mothers at RSUD Walanda Maramis.